Membangun Brand Image Melalui Konten Instagram (Studi Kasus: CV Bumi Agro Technology) - Syafatulloh, Gareth Insan; Setiawan, Iwan (Universitas Galuh, 2026)
This research analyzes the role of Instagram content implementation in building CV Bumi Agro Technology's brand image within the agribusiness sector, addressing the challenge of reflecting digital credibility aligned with the company's core values. Employing a descriptive qualitative case study approach, with data collected via in-depth interviews, participant observation, and a documentation study, this research explores the desired digital branding vision, the systematic content implementation process, and audience perceptions. The findings indicate that the structured Instagram content implementation process—encompassing strategic planning (such as blueprints and key messages) and the design of visual and video content (educational reels, informative written content, and student intern involvement) with consistent design elements—successfully conveys the company's core values like modern, innovative, environmentally friendly, and sustainable agriculture. This approach also proactively contributes to changing the stigma of agriculture into an attractive and prestigious field. Audience perception of the brand image underwent a significant positive shift following content optimization since July 2024, evidenced by a more interactive and professional account, improved visual quality, content consistency, and innovation. Audiences consistently grasped the company's core values, formed emotional connections through humanistic storytelling, and successfully responded to calls to action (CTAs), which built their intent and conviction. This research recommends strengthening the continuity of digital narratives and fostering more active audience engagement to cultivate deeper emotional connections. The findings of this study can also serve as a reference for other agribusiness companies in utilizing social media as a resourceful and strategic branding tool.